Bibliometric Analysis of Collaborative Governance for Smart City Program - Marliani, Marliani (Journal Governance Society, 2025)
The rapid urbanization in Indonesia over the past two decades has brought complex governance challenges, particularly in managing smart city programs that require multi-stakeholder collaboration, technological innovation, and inclusive policy-making. While collaborative governance has been widely studied in global contexts, its application in Indonesia demands adaptation to local socio-cultural values such as mutual cooperation and deliberative consensus. This study aims to map and analyze the development of research on collaborative governance for smart city programs in Indonesia from 2010 to 2024, identifying knowledge structures, thematic trends, and collaboration networks. Employing a quantitative bibliometric approach, data were collected from the Web of Science, Scopus, and Google Scholar databases using systematically designed search strings, screened through the PRISMA protocol, and analyzed with Bibliometrix and VOSviewer software. The findings indicate a steady growth in publications, with seminal works by Ansell & Gash (2008) and Nam & Pardo (2011) serving as key theoretical foundations. Research increasingly integrates governance theory with technology adoption and community engagement, supported by international collaborations involving countries such as the United States, Australia, and the United Kingdom. However, gaps remain in operationalizing collaborative governance at the local level and aligning national policies with municipal autonomy. This study concludes that advancing Indonesia’s smart city agenda requires governance frameworks that are both technologically forward looking and culturally grounded. The bibliometric insights provide a roadmap for policymakers, academics, and practitioners to design sustainable, inclusive, and context-sensitive urban governance strategies that bridge global innovations with local realities